Resin-Based Nanocomposites Coated Proppants as Scale Inhibitor Carrier and Slowly Releasing Container - Alzanam, A.A.A. (Unconventional Resources Technology Conference (URTEC), 2021)
Comparable to conventional oil and gas reservoirs, unconventional reservoirs can often exhibit scale formation that reduces well production. Although current squeeze treatment is the optimum way to prevent scale from depositing, it lacks certain aspects such as adsorption ability and retention time within the rock formation. It is well known that proppant is considered as one of the main additives in simulating unconventional wells, and its primary function is to maintain a conductive fracture during well production. Beyond that, it can serve as a matrix to deliver chemicals deep into the reservoirs. Therefore, in this work, resin-based nanocomposites coated proppants were developed to act both as a strong scale inhibitor carrier and slowly releasing containers. Porous ceramic proppants were treated with carbon-based nanomaterials such as multi-wall carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs). Then, infused with scale inhibitor and coated with an ultra-thin layer of Polyurethane resin-based carbon nanocomposites via novel spray coating technique. Infused coated proppants were characterized using Field Emission Scanning Electron Microscope (FESEM) and Energy Dispersive X-Ray Analyzer (EDX). Further work was carried out to analyze the proposed proppants' mechanical characteristics, thermal stability, and potential to enhance the inhibition lifetime. FESEM results revealed that an ultra-thin uniformed coating layer was successfully established. The EDX results confirmed that the proppants surface was uniformly covered with MWCNTs and GNPs. The API crush test showed that the proposed MWCNT reinforced resin-coated proppant and GNP reinforced resin-coated proppant were capable of lessening the proppant pack compaction by 23 and 21, respectively compared to untreated infused porous ceramic proppant. With more than 55 reduction in fines production. Thermo-Gravimetric Analyses (TGA) disclosed a significant increment in thermal stability, which reaches up to 300Â°C due to MWCNTs and GNPs' addition as reinforcing nanofillers. The residual test indicates that proposed proppants recorded a 40 reduction of released inhibitor than the infused porous ceramic proppants. The kinetics analysis revealed that intraparticle diffusion dominated the desorption of scale inhibitor from the proposed proppants, explaining the slow desorption rate they exhibited. The remarkable mechanical, thermal, and scale inhibition characteristics of the proposed proppants allow them to be a potential multifunctional proppant in oil and gas wells. Â© 2021 Unconventional Resources Technology Conference (URTeC)